PENGARUH STRATEGI PENYULUHAN DAN MOTIVASI PEMELIHARAAN KESEHATAN LINGKUNGAN TERHADAP PENGETAHUAN IBU RUMAH TANGGA TENTANG SAMPAH - Endang Surahman; Yoni Hermawan (Bumi Lestari Journal of Environment, 2011)
Knowledge of garbage problem is important for a community. A study has been conducted at Singkup Village of Tasikmalaya, West Java. The objective was to find out the effects of extension strategy, and the motivation of environment healthy care on the knowledge about garbage of the housewives in the village, which has a dumping site. The design was a 2 x 2 factorial with a sample of 60 women, selected at random. The results show that the housewife’s knowledge about garbage was better by cooperative extension strategy than by the tutorial strategy. The high motivation for healthy care of environment was better by cooperative extension strategy; and for the low motivation healthy care, the tutorial extension strategy better than the cooperative way. The interaction was found between extension strategy and the healthy environment care on knowledge about garbage.